KONTRIBUSI KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KOMITMEN KERJA GURU PAI MTs N DI KABUPATEN LIMA PULUH KOTA - Leni Marwati (Ensiklopedia of Journal, 2023)
This research is motivated by the reality in the field, where the tasks carried out by madrasa teachers are getting heavier with the times. So it is not enough if the teacher only has good academic skills, but he also has to have mature emotional management skills and the meaning and deepening of life values. These two abilities can be categorized into emotional intelligence and spiritual intelligence.The method used in this research is quantitative research using the Ex Post Facto approach. This method is used to examine cause-and-effect relationships and see the various problems that arise today. The hypotheses in this study are: (1) There is a contribution of Emotional Intelligence to the Work Commitment of PAI MTsN teachers in Fifty Cities District. (2) There is a Contribution of Spiritual Intelligence to the Work Commitment of PAI MTsN Teachers in Fifty Cities District. (3) There is a joint contribution of Emotional Intelligence and Spiritual Intelligence to the Work Commitment of MTsN PAI Teachers in Fifty Cities District. The population of this study were all PAI teachers with the status of State Civil Apparatus (ASN) and spread to seven MTsN in Lima Puluh Kota Regency with a total of 46 people. The number of samples of researchers as many as 40 people. Sampling in this study using the empirical formula recommended by Isaac and Michael. Data collection techniques using a questionnaire.The results of this study indicate that: (1) there is a significant contribution of emotional intelligence to the work commitment of PAI MTsN teachers in Lima Puluh Kota Regency, which is 0.591 with a correlation of determination of 0.349 or 34.9%, (2) there is a significant contribution of spiritual intelligence on the work commitment of PAI MTsN teachers in Lima Puluh Kota Regency, which is 0.410 with a correlation of determination of 0.168 or (16.8%), (3) there is a significant contribution of emotional intelligence and spiritual intelligence together to the work commitment of PAI MTsN teachers in the District of Fifty Cities, which is 0.591 with a correlation of determination of 0.349 or (34.9%).